Cinema and Phenomenology: Toward a Reflection on the Phenomena of Modernity as the Kingspin for the Origin of Cinematographic Language. - Santos, Marcelo Moreira (Signs - International Journal of Semiotics, 2008)
This article aims at reflecting on cinematography, its origin and development along with the phenomenon of modernity. The utilization of Charles S. Peirce’s Phenomenology in this study does not refer to the reception of cinematography, but to our aspiration to observe through which parameters, a language such as the one in movies, developed itself, in other words, how a kind of logic, esthetics and ethics found in the movies consolidated itself. Departing from such premises, the first step was to observe the phenomena in the metropolis through the philosophical texts of Walter Benjamin and the recent book organized by Leo Charney and Vanessa R. Schwartz: “The Movies and the Invention of Modern Life”; in search of a dialog between Peirce, Modernity and the Cinema.